DETERMINING THE RELATION BETWEEN PERSONALITY TRAITS AND LIFE SATISFACTION LEVELS OF BODY BUILDING TRAINERS - GEÇER, Alen; TAZEGÜL, Ünsal (IJRDO- Journal of Educational Research, 2016)
The aim of this research was to determine the relation between personality traits and life satisfaction levels of body building trainers. Sample of the study consisted of 76 body building trainers who volunteered in the study. Life Satisfaction Scale and Reviewed Eysenck Personality QuestionnaireAbbreviated Form were used as data collection means. SPSS 20 package program was used in data analysis. “Kolmogorov-Smirnov” test was used so as to determine that data have normal distribution and “Anova-Homogeneity of Variances” test was applied to determine homogeneity of the data and it was determined that data are homogeneous and have a normal distribution. After this first review, use of parametric test method was decided for statistical analysis of the data. Descriptive statistics and Pearson correlation and Regression analysis were used in data analysis. As a result of the study, it was found that body building trainers have high score in extroversion and that there is a negative way medium level relation between life satisfaction score and neuroticism and psychoticism dimensions of body building trainers. Key Words: Body building, personality, life satisfaction.